Well‐being‐oriented human resource management practices and employee performance in the Chinese banking sector: The role of social climate and resilience - Cooper, Brian; Wang, Jue; Bartram, Timothy; Cooke, Fang Lee (Human Resource Management, 2019)
Drawing upon positive psychology and a social relational perspective, this article examines the relationship between well‐being‐oriented human resource management (HRM) practices and employee performance. Our multilevel model examines relationships among collectively experienced well‐being‐oriented HRM practices, social climate (characterized by trust, cooperation, and shared codes and language that exist among individuals within the organization), employee resilience, and employee (in‐role) performance. Based on the two‐wave data obtained from 561 employees and their managers within 62 bank branches in 16 Chinese banks, our multilevel analyses provide support for our four hypotheses. First, we found a positive relationship between well‐being‐oriented HRM practices and social climate. Second, social climate mediated the relationship between well‐being‐oriented HRM practices and employee resilience. Third, we found a positive relationship between resilience and employee performance. Finally, employee resilience mediated the relationship between social climate and employee performance. This study is one of the first to unpack the social mechanisms through which well‐being‐oriented HRM practices increase development of resilience and subsequent employee performance at the workplace, namely through influencing group feelings of social climate.